Culturally responsive pedagogy for the promotion of understanding Mathematics: The case of rural situated primary schools in Post-apartheid South Africa - Zingiswa Jojo (Interdisciplinary Journal of Sociality Studies)
The language of instruction, awareness, and creativity are at the centre of the realities faced by both mathematics teachers and learners, shaped by a socio-political history whose impact and legacy transcend generations in South Africa. Consequently, the dire state of mathematics education in South Africa remains a cause for concern. Recognising the need to conceptualise and develop culturally responsive pedagogy, this paper presents the results from the third phase of a three-year longitudinal study focused on teachers' journeys in infusing indigenous knowledge when teaching geometry to senior primary learners in rural schools. This qualitative study, which followed a case study design, explored several approaches to discussing, teaching, and considering an immediate, perpetual, operative, and discursive approach as culturally disruptive pedagogy used as an indigenous way to promote geometric understanding. Observations and semi-structured interviews were conducted with two purposefully selected participants after their lesson presentations to allow them to clarify, elaborate, and introduce more detail, enriching their explanations of the artefacts used. Results indicated that teachers’ references to several artefacts and indigenous activities, such as using straws, wool, and staplers, promoted the understanding of the construction of prisms and pyramids. Recommendations include training mathematics teachers to prepare lessons that incorporate indigenous knowledge and to explore ethnomathematics as a culturally responsive teaching strategy, particularly in contextualising mathematical geometry learning, so that this concept can have relevance and meaning for rural students.